Epigenetic programming underpins B cell dysfunction in human SLE - Scharer, Christopher D.; Blalock, Emily L.; Mi, Tian; Barwick, Benjamin G.; Jenks, Scott A.; Deguchi, Tsuneo; Cashman, Kevin S.; Neary, Bridget E.; Patterson, Dillon G.; Hicks, Sakeenah L.; Khosroshahi, Arezou; Eun-Hyung Lee, F.; et al. (Nature immunology, 2019)
Systemic lupus erythematosus (SLE) is characterized by the expansion of extrafollicular pathogenic B cells derived from newly activated naive cells. Although these cells express distinct markers, their epigenetic architecture and how it contributes to SLE remain poorly understood. To address this, we determined the DNA methylomes, chromatin accessibility profiles and transcriptomes from five human B cell subsets, including a newly defined effector B cell subset, from subjects with SLE and healthy controls. Our data define a differentiation hierarchy for the subsets and elucidate the epigenetic and transcriptional differences between effector and memory B cells. Importantly, an SLE molecular signature was already established in resting naive cells and was dominated by enrichment of accessible chromatin in motifs for AP-1 and EGR transcription factors. Together, these factors acted in synergy with T-BET to shape the epigenome of expanded SLE effector B cell subsets. Thus, our data define the molecular foundation of pathogenic B cell dysfunction in SLE. Systemic lupus erythematosus (SLE) is characterized by autoantibodies produced by pathogenic B cells. Boss, Sanz and colleagues show that SLE-associated epigenetic changes exist in gene regulatory programs in resting naive B cells, before their differentiation into antibody-producing plasma cells.